Biomass yield, quality and acceptability of selected grass-legume mixtures in the moist savanna of West Africa - Olanite, J.A.; Tarawali, Shirley A.; Akenova, M.E. (2004)
In order to identify options suitable for providing livestock feed in the wetter part of the moist savanna, the DM yield, botanical composition, crude protein, in sacco digestibility and neutral detergent fibre of combinations of 4 herbaceous legumes and 2 grasses were evaluated between June 1994 and December 1995 at Ibadan, south-western Nigeria. The legumes, Stylosanthes guianensis, Aeschynomene histrix, Centrosema pubescens and Chamaecrista rotundifolia, were each planted in combination with Brachiaria ruziziensis and Cynodon nlemfuensis. Beginning from one year after planting, the mixtures were mob-grazed 4 times at 8-weekly intervals following DM yield estimation.